Bacillus subtilis and Pichia farinose mixture improves growth performance and nutrient absorption capacity in broiler chicks - Wang, Huan; Fu, Lu; Zhang, Jian Ying; Kim, In Ho (Frontiers in Veterinary Science, 2023)
This study evaluated the effects of dietary supplementation of Bacillus subtilis and Pichia farinose mixture (BPM) on growth performance, apparent ileal digestibility, cecal bacteria counts, small intestinal morphology and digestive enzymes activities, and jejunal nutrient transporters gene expression in broiler chicks. A total of 768 one-day-old Ross 308 broiler chicks were randomly assigned into 3 groups based on the initial body weight (42.00 ± 0.08 g). The experimental periods were 35 days. There were 16 replicates per group and 16 birds per cage. Dietary treatments included a basal diet supplemented with 0, 0.1, or 0.2% BPM to form CON, BPM0.1 (consisting Bacillus subtilis with 1.0 × 107 viable spore and Pichia farinose with 1.0 × 107 viable spore per kg diet), and BPM0.2 (consisting Bacillus subtilis with 2.0 × 107 viable spore and Pichia farinose with 2.0 × 107 viable spore per kg diet) groups. Dietary supplementation of graded levels of BPM has positive effects on growth performance of broiler chicks, manifesting in the increase of body weight gain during days 1-35 as well as the decrease of feed conversion ratio during days 1-7, 21-35, and 1-35. Moreover, BPM supplementation positively improved ileal energy and crude protein digestibility, increased Lactobacillus counts, optimized intestinal morphology, enhanced intestinal digestive enzymes activities, and upregulated jejunal SGLT-1, GLUT-2, and PEPT-1 expression. Therefore, BPM supplementation improved growth performance of broiler chicks, which was partially related to the improvement in intestinal nutrient absorption capacity.